2021
DOI: 10.3389/fpsyg.2021.660062
|View full text |Cite|
|
Sign up to set email alerts
|

Cognitive Control and Ruminative Responses to Stress: Understanding the Different Facets of Cognitive Control

Abstract: Rumination has been linked to the onset and course of depression. Theoretical models and empirical evidence suggest that deficits controlling negative material in working memory underlie rumination. However, we do not know which component of cognitive control (inhibition, shifting, or updating) contributes most to rumination, and whether different components predict the more maladaptive (brooding) versus the more adaptive (reflection) forms of rumination. We aimed to advance theory and research by examining th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 65 publications
(96 reference statements)
0
7
0
1
Order By: Relevance
“…Moreover, using the emotional Stroop task measuring inhibitory control and the affective version of the two-back task for assessing updating, Zareian et al . ( 2021 ) reported that inhibition difficulties can predict brooding and reflection (two components of rumination), while updating cannot. In recent years, a comprehensive meta-analysis of 34 studies including 3066 participants put forward that research on the relationship between rumination and two other subcomponents of EF (i.e., shifting and updating) have not yet yielded consistent results, while there is an obvious negative correlation between rumination and inhibitory control (Yang et al ., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, using the emotional Stroop task measuring inhibitory control and the affective version of the two-back task for assessing updating, Zareian et al . ( 2021 ) reported that inhibition difficulties can predict brooding and reflection (two components of rumination), while updating cannot. In recent years, a comprehensive meta-analysis of 34 studies including 3066 participants put forward that research on the relationship between rumination and two other subcomponents of EF (i.e., shifting and updating) have not yet yielded consistent results, while there is an obvious negative correlation between rumination and inhibitory control (Yang et al ., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…One such cognitive style is rumination, defined as the individual’s passive tendency to dwell repetitively on the meaning and causes of one’s mood symptoms (Watkins & Nolen-Hoeksema, 2014). Ruminative thinking, usually displayed more frequently by adolescent girls than boys (e.g., Johnson & Whisman, 2013) has been constantly linked to depression (e.g., Zareian et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Third, since the MIDUS Refresher Daily Diary Project was a large-scale study conducted over the telephone rather than in the laboratory, we were unable to control for a singular initial negative event that triggered rumination across all participants. While some studies have focused on specific forms of state rumination, such as following an interpersonal offense (McCullough et al, 2007) or a stressor (Grant & Beck, 2010; LeMoult et al, 2013; Zareian et al, 2021), state rumination has been shown to occur across a range of other contexts of daily life in which its antecedent may not be so readily identifiable. For instance, state rumination may arise in response to a spontaneous thought that focuses on unattained goals (Marchetti et al, 2016).…”
Section: Discussionmentioning
confidence: 99%